การพัฒนาเครื่องมือวัดปัญญาด้านการรับรู้ภาวะการเคลื่อนไหวของร่างกาย - สมบูรณ์ อินทร์ถมยา (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
To develop the measurement instrument of the bodily-kinesthetic intelligence and to construct th criteria of the norms of the T-score. The study procedures were divided into 4 steps (1) Determine the components of the bodily-kinesthetic intelligence; (2) Construct the measurement instrument of the bodily-kinesthetic intelligence and the manual for using this test; (3) Find of the quality of the test by testing content validity, construct validity and reliability; and (4) construct the criteria of the norms of the measurement instrument of the bodily-kinesthetic intelligence. It was found that the bodily-kinesthetic intelligence composed of 3 components. There were (1) body awareness : laterality, static balance, and dynamic balance (2) body image : walking on the track and range of motion in curvelinear (3) body relationship to surrounding objects in space: directionality and weight discrimination. This test consisted items for testing the bodily-kinesthetic intelligence and it was feasible and applicable in schools situation. It had content validity at 0.76 (IOC) and construct validity was statistically significant at .01 level and reliability also was statistically significant at .01 level in 4 items for male samples (1) alternate dribbling r = 0.55; (2) stork stand r = 0.49; (3) dynamic walking balance r = 0.58; and (4) directional anticipation r = 0.35 and 2 items for female samples : (1) stork stand r = 0.88; and (2) dynamic walking balance r = 0.63 and was statistically significant at .05 level in 1 item for female samples : alternate dribbling test r = 0.26. The criteria of the norms of student at level 2 were also developed according to the gender by making the level of performance in 5 levels : very good, good, fair, low and very low. The result indicated that : the measurement instrument of the bodily-kinesthetic intelligence had 3 components which consisted of 7 test items; had the quality of the test both validity and reliability; and had the T-score that could take it for instruction physical education.